Digital mind mapping as a pedagogical tool to support the student’s business plan writing performance - Farida Amansyah; Sahril Nur; Ismail Anas (UNIB Press, 2023)
The article presents a study focusing on using Digital Mind Mapping (DMM) by students to develop a business plan concept and enhance their ability to plan and organize a new business roadmap. In line with the task-based language teaching approach and Ellis's framework for designing task-based lessons, the study investigates the students' practices of creating meaning and their reflections on using DMM. The research consists of three main stages: pre-task, during-the-task, and post-task activities. Twenty-three students enrolled in a Business English course participated in the study, and qualitative data, including business plan diagrams, student-created business plans, and reflection sheets, were collected and analyzed. The findings reveal that the students reflected positively on their experience with DMM, as the task stimulated their active participation, exploration, autonomy, and engagement throughout the writing process. This study contributes to the existing literature on task-based language teaching by examining the effectiveness of Digital Mind Mapping in facilitating students' business planning and organizational skills. Additionally, it provides insights into exploring the long-term impact of utilizing DMM in various language learning contexts and investigates potential strategies for optimizing its implementation in business English courses.